Advertising in accounting firms: Empirical Perspective - Hadri Kusuma (Economic Journal of Emerging Markets, 1994)
Advertising becomes an interesting tool for the accounting profession in the face of increased competition. Accounting firms today realize that advertising will play an important role in their overall success.